Review of Value at Risk estimation methods - Stefaniak, Radosław (Research Papers of Wrocław University of Economics, 2018)
On a daily basis, managers in risk management teams use a number of methods to manage various types of risk. One of the most popular methods of measuring market risk is Value at Risk. Estimation of Value at Risk gives a possibility to determine a loss, which can occur or can be exceeded with a given probability and tolerance level. Moreover, this measure of risk shows in just one number entire risk of the portfolio. In addition, various methods and probability distributions can be used to estimate Value at Risk. A goal of this paper is the evaluation of Value at Risk estimation methods on the basis of backtesting results. In the empirical part, the data for 4 investment portfolios was used. The portfolios were diversified in terms of geographic location of firms that were taken into consideration
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 173-183
Keywords: value at risk; estimation; backtesting; investment portfolio; wartość zagrożona; estymacja; testy wsteczne; ryzyko całkowite; portfel inwestycyjny